TOWARDS A COMPETITIVE PERUVIAN PENSION SYSTEM - Hidalgo Tupia, Manuel Alberto (2016)
The study gathers perceptions about the Peruvian pension system regarding the possibility of optimizing the financial management of the resources of the National Pension Fund, aiming to create a greater profitability and competitiveness with respect to the system, generating a real alternative the private pension system.A documentary analysis was carried out and surveys were applied to three groups of informants: organized social sector, academic specialists, and pension system managers. The research problem was: How does the intervention of the ONP (National Pension Bureau) with professionalization of investments affects the competitiveness of the Pension System in Peru? The results obtained from the application of the surveys to specialists and representatives of the social sector were that the professionalization of ONP investments is possible and desirable, requiring regulatory and administrative changes and that should be applied according to the investment theory In portfolio. Plus, given the conditions, that scenario would generate greater competitiveness in the pension system as a whole, positively impacting the stability and growth of the capital market and the national economy, also positively impacting the welfare of pensioners and contributors.